Statins and Nonadherence: Should We RELATE Better?. (September 2015) - Turin, Alexander; Pandit, Jay; Stone, Neil J.
Statin nonadherence is a major challenge to optimal management. Patients nonadherent to statin therapy do not receive the expected benefit relative to the degree of low-density lipoprotein cholesterol (LDL-C) lowering obtained. This is important because new evidence guidelines recommend statins as the first-line therapy for those in high-risk groups (secondary prevention, patients with diabetes 40-75 years of age, and LDL-C ≥ 190 mg/dL) and in selected primary prevention patients. Statin assignment in the latter group occurs only in those with an estimated ≥7.5% 10-year atherosclerotic cardiovascular disease risk after shared decision making in a clinician–patient risk discussion. However, in numerous studies, statin nonadherence shows little or no benefit in reducing cardiovascular events or mortality compared to placebo, effectively negating the risk reduction expected from statin use and concomitantly increasing the total cost of health care. The causes and solutions for nonadherence are multifactorial and include patient, clinician, and health system factors. We believe that a clinician–patient partnership that facilitates patients' understanding of the potential for optimal benefit with the least adverse effects is an important first step toward improving adherence. A transtheoretical model of stages of behavior change helps clinicians address many of the common factors limiting adherence to statins. We conclude with a teaching tool emphasizing a structured approach to statin therapy with patient-centered risk discussions.